Simon Rottenberg and Baseball, Then and Now: A Fiftieth Anniversary Retrospective - Sanderson, Allen R.; Siegfried, John J. (Journal of Political Economy, 2006)
Fifty years ago this Journal published Simon Rottenberg’s “The Baseball Players’ Labor Market,” the first professional journal article in sports economics. In this retrospective we review some of his insights and analyses with regard to competitive balance, constraints on payroll and freedoms to contract, revenue sharing, territorial rights, and the supply of talent. We also note subsequent industry developments Rottenberg could not have anticipated and identify where he was ahead of his time.